2020
DOI: 10.1002/jcp.29484
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0004277 contributes to malignant phenotype of colorectal cancer by sponging miR‐512‐5p to upregulate the expression of PTMA

Abstract: In recent years, extensive reports have been published concerning the molecular mechanism underlying the occurrence and progression of colorectal cancer. Circular RNAs (circRNAs) have been identified as important modulators in the biological processes of colorectal cancer. Microarray analysis unveiled that differential circ‐0004277 expression was identified in tissue samples of colorectal cancer. High circ‐0004277 expression was then verified in tissue samples and cell lines of colorectal cancer via qRT‐PCR. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…1 ). Interestingly, except miR-500a-3p, the other 3 miRNAs have been reported to inhibit the malignant phenotype of tumors [ 18 20 ]. Then, further upstream analysis was conducted and SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2 and AC026362.1 were lncRNAs that could bind to the above 4 miRNAs and be degraded.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Interestingly, except miR-500a-3p, the other 3 miRNAs have been reported to inhibit the malignant phenotype of tumors [ 18 20 ]. Then, further upstream analysis was conducted and SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2 and AC026362.1 were lncRNAs that could bind to the above 4 miRNAs and be degraded.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the present study indicated that, as a target of miR-206, PTMA overexpression debilitated the inhibitory role of CYTOR depletion in NSCLC cell radiosensitivity, as evidenced by the improved Ki67-positive rate. As a downstream factor in the ceRNA network, the upregulation of PTMA caused the outgrowth of exacerbated colorectal cancer ( 61 ). Furthermore, PTMA exhibited a negative association with the radiosensitivity of colorectal cancer ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hsa_circ_0004277 promotes the proliferation of colorectal cancer cells, acting as a miR-512-5p sponge to upregulate the expression of an oncogene PTMA (Prothymosin alpha) in CRC [ 135 ]. The overexpressed PTMA induces the proteasome degradation of tumor suppressor p53 (wild type) through ubiquitination by Mdm2 (E3 ubiquitin-protein ligase), and thus PTMA is free to exert its oncogenic functions.…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%
“…Bcl-2 and Bax are also significantly changed by circCSNK1G1 (hsa_circ_101555, hsa_circ_0001955) [ 183 ]. Silencing of hsa_circ_0004277 significantly increases caspase-3 activity [ 135 ]. CircABCB10 (hsa_circ_0008717) negatively regulate miR-326 and upregulates CCL5 (Chemokine (C-C motif) ligand 5) to suppress cell ferroptosis and apoptosis [ 198 ].…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%